Use of convex glass to improve driving safety in Sukahurip Village - Karim, Muhammad Aqmal Nurilshifa; Akbarulah, Bravian Ariq; Katiah, K. (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Driving safety is a severe challenge experienced by Sukahurip Village. In 2021, 306 accidents were recorded, especially on roads with sharp bends. The Sukahurip Village 2023 UPI KKN Student Team took the initiative through this service program to install convex mirrors on roads with sharp bends. The installation of this convex mirror as a 2023 UPI KKN student service program in Sukhurip Village is an effort to reduce the number of accidents and improve driving safety in Sukahurip Village. Another objective is to evaluate the impact of convex mirrors on improving traffic safety in rural areas. This service method is carried out through a direct approach in the area where the service is carried out by installing convex mirrors with a focus on broadening the driver's view and increasing awareness of road conditions. The results show a reduction in traffic accidents in the area because the convex mirror increases the viewing angle for the driver and allows a quicker response to road situations. This can certainly be a solution and a significant contribution for village communities to reduce the risk of accidents. The mirror installation involved collaboration between UPI 2023 KKN students and Sukahurip Village residents, providing concrete benefits for road safety in the village. It is hoped that one of the programs in this service activity can become the basis for similar programs regarding the importance of simple innovations such as convex mirrors in driving safety in rural areas.